Mengoptimalkan Implementasi UU No. 27 Tahun 2022 Dengan Penetration Test Dan Vulnerability Assessment Pada Kasus Pembobolan Data Aplikasi Dana - Tabitha Fransisca Romauli Nababan; Shevanna Putri Cantiqa (Pusat Riset dan Inovasi Nasional, 2024)
Data security in digital financial applications such as mobile banking, e-wallets, and online payment services is very important. However, there are many security risks lurking. Irresponsible parties can exploit security gaps to steal personal information. The ITE Law regulates the limitations, obligations, and responsibilities of parties involved in electronic systems, including service providers, data managers, and users as well as sanctions for cybercriminals. One of the main weaknesses in a financial application is the lack of strict and consistent security standards. Due to the many acts of cybercrime, it is important for companies to take preventive measures, one of which is through Vulnerability Assessment and Penetration Testing (VAPT). VAPT can help identify and fix vulnerabilities in applications before they are exploited by cybercriminals